2019
DOI: 10.23887/ijssb.v3i3.21060
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Catur Purusa Artha and Capital Structure as The Maximization Key of Financial Performance in LPD Buleleng District

Abstract: The purpose of this study is to examine the implementation of the value of Catur Purusa Arthaand capital structure, as the main foundation of business strategy to create maximum financial performance of LPD in Buleleng Regency. The study population was all active LPDs in Buleleng Regency. Sampling in this study using random sampling techniques to obtain as many as 60 observational data. The data analysis technique used in this research is the Component based SEM method, Partial Least Square (PLS). The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 5 publications
1
5
1
Order By: Relevance
“…It shows that the type of clan culture does not sufficiently support the implementation of MSS in the LPD in an organizational manner that should be and is supported by a professional attitude in carrying out work following the values of a good LoC. The study results in table 2 show evidence, not in line with the research of Trisnawati et al (2019), which proves that religious values influence the financial performance of LPDs in Buleleng Regency as part of the organizational culture and capital structure of LPDs.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…It shows that the type of clan culture does not sufficiently support the implementation of MSS in the LPD in an organizational manner that should be and is supported by a professional attitude in carrying out work following the values of a good LoC. The study results in table 2 show evidence, not in line with the research of Trisnawati et al (2019), which proves that religious values influence the financial performance of LPDs in Buleleng Regency as part of the organizational culture and capital structure of LPDs.…”
Section: Resultsmentioning
confidence: 73%
“…Pancadana and Parwata (2012) analyzed and formulated the concept of Catur Purusa Artha as the basis for the business activities of the Village Credit Institution (LPD) of Pakraman Kikian Village. The values of Catur Purusa Artha affect the financial performance of LPDs in the Buleleng Regency (Trisnawati et al, 2019). Suryanata (2019) found that the synergy of the LPD, traditional village prajuru, and indigenous village communities affected the economic development of the Kedonganan Traditional Village community.…”
Section: Introductionmentioning
confidence: 99%
“…Which consists of Dharma, Artha, Kama and Moksa which when associated with the Resource Based View (RBV) Theory is an intangible asset. The concept of dharma underlies business activities on the basis of goodness through service to customers (Erik Trisnawati et al, 2019). This BUMDes management model combines a touch of cultural values of catur purusa artha which uses dharma as its basis combined with product innovation will be a strength in maintaining business continuity so that a holding company in the style of a traditional village can be realized.…”
Section: Methodsmentioning
confidence: 99%
“…The implementation of the dharma concept in the cultural values of Catur Purusa Artha as a new adaptation of BUMDes management will encourage administrators to make more appropriate product service innovation choices so that they can maintain business continuity in the future. The concept of business management based on this dharma has previously been applied to LPDs in Buleleng district and managed to maximize their financial performance (Erik Trisnawati et al, 2019). An externally oriented organizational culture is central to excellence in product development based on customer desires.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation